A mediação tecnológica como aporte aprendente na formação médica - Honório, Carla Paiva Feitosa (2020)
The advent of the network society and the emergence of digital culture permeate and are dimensioned by profound subjective-social transformations, whose articulations occur from the advent of cyberspace, an immaterial and cross-border place, interconnected and potentially nuanced by information and communication, with meaningful and collaborative promises for teaching and education. Thus, currently, the understanding that digital information and communication technologies are inseparable from human life points to the need to reflect on teaching-learning perspectives in higher education articulated with the multiple paths of cyberspace, from which virtual learning environments (VLE) have provided innovative didactic-pedagogical resources for the development of educational processes. In this sense, this study aims to understand medical training in cyberspace, based on technological mediation as a learning input at the Nova Esperança School of Medicine, in João Pessoa – PB. Regarding the methodological path, this investigation is characterized as field research with a qualitative approach and of the descriptive, exploratory type. As data collection instrument the semi-structured interview was used, which was conducted with the management course representative and a sample of four professors and four students from the school. The collected data were coded and interpreted in the light of content analysis (categorical). The results revealed that the actors of the teaching-learning process of the higher education institution studied acknowledge the importance of technological mediation as a learning input in the Medicine course, being of great value to make the activities in the classroom more attractive, as well as serving as an educational contribution through VLEs, since complementary materials are made available and remote activities are carried out, aiming at making teaching more dynamic, fostering learning and solidifying knowledge. Even in the face of some registered disadvantages, it was possible to see how the interactions between teachers and students take place, whose connectivity provides the flexibility of time and space, allowing students to organize their activities. With the social isolation imposed by the pandemic of SARS-CoV-2/Covid-19 (Coronavirus), the research concludes that the use of digital information and communication technologies in the teaching-learning process in Medicine was intensified, emphasizing the technological apparatus as promising and fundamental learning inputs, through digital media.